Alleviation of DSS-induced colitis by Meconopsis polysaccharides correlated with reduced PI3K/AKT signaling and gut microbiome diversity - Dai, Jun; Wang, Weidong; He, Fangfang; Wang, Yujuan; Zou, Denglang (Frontiers in Pharmacology, 2025)
IntroductionInflammatory bowel disease (IBD) is a recurrent gastrointestinal disorder that significantly impacts patients’ quality of life globally. This study focuses on the polysaccharides (MP) extracted from Meconopsis integrifolia, to investigate its role in alleviating DSS (dextran sulfate sodium)-induced colitis in mice.MethodsThe study commenced with a comprehensive chemical characterization of Meconopsis polysaccharides. Subsequently, the colitis-alleviating activity of MP was validated through in vivo experiments.ResultsThe results revealed that MP is primarily composed of ten monosaccharides, exhibits good thermal stability, and has a relatively uniform molecular weight distribution. In vivo experiments demonstrated that MP significantly mitigated DSS-induced weight loss, increased DAI, colon shortening, and tissue damage in mice. Furthermore, MP reduced the levels of inflammatory cytokines such as IL-1β, TNF-α, and IL-6 in serum. Mechanistically, MP exerted its anti-inflammatory effects by inhibiting the activation of the PI3K/AKT signaling pathway. Additionally, MP promoted gut microbiota diversity and regulated SCFA concentrations, contributing to an improved intestinal microenvironment and alleviation of colitis symptoms.DiscussionOur findings highlight the superior effectiveness of Meconopsis polysaccharides in alleviating DSS-induced colitis and open new avenues for targeted therapeutic strategies in the treatment of IBD.